Optimization of texture design parameters for reduction of friction coefficient based on design of experiments and the modified acceleration gradient method - Hideto ODA; Takahiko KURAHASHI; Demófilo MALDONADO CORTÉS; Laura PEÑA-PARÀS (Journal of Fluid Science and Technology)
In this paper, we propose a new optimization procedure for texture design parameters that combines design of experiments and the modified acceleration gradient method. For the design of texture parameters, it is necessary to determine the optimal combination of number, placement angle, spacing and horizontal shape of texture elements. There are many possible combinations of design parameters, so it is necessary to decide select efficiently. In a previous study, we clarified that frictional force can be reduced by varying the texture depth (Arata et al., 2022). In this study, we investigate a method of determining texture design parameters based on design of experiments and the modified acceleration gradient method. Circular and rectangular shapes are generally employed as the horizontal shapes of texture elements, but Maldonado- Cortés et al. (2021) report that an s-shaped texture more effectively reduces the friction coefficient. In this investigation into the reduction of friction coefficient, numerical experiments were performed that included this s-shaped texture.